Socio-environmental change and flood risks: the case of Santiago de Chile - Ebert, Annemarie; Welz, Juliane; Heinrichs, Dirk; Krelleneberg, Kertsin; Hansjürgens, Bernd (ERDKUNDE, 2010)
The extreme concentration of values, people, infrastructure and economic prosperity in megacities creates chances but also makes the population vulnerable to extreme events and natural catastrophes. There is a degree of consensus that, particularly in large agglomerations, hazardous events (e.g. storms, floods, landslides) are not solely the result of natural phenomena, but are rather the result of the interaction between (changing) natural and social/anthropogenic factors. Furthermore, risks resulting from this combination are distributed unevenly across the population: poorer urban households are more at risk to ‘natural’ hazards. This paper investigates these assumptions. It explores the social and environmental dimensions of land use changes and how they relate to flood risk. Its geographic focus is Santiago de Chile. This rapidly changing megacity with about 6 million inhabitants is located in the Maipo river basin between the central and the coastal Andean cordilleras. The study firstly examines flood risk by considering natural factors and anthropogenic land use change. Secondly, it explores processes of socio-spatial differentiation, aiming to evaluate their relevance for the attenuation of flood risk and its distribution across various socio-economic status groups. Thirdly, it provides a synthesis of the linkages between land use and socio-spatial differentiation processes leading to socio-environmental change and flood risks. The data used for the analysis is based on multi-temporal remote sensing data and statistical data from the Chilean National Census of Population and Housing. The results demonstrate that anthropogenic land use changes increase the exposure of residents to potentially hazardous events and aggravate flood hazards by increasing the surface water runoff after precipitation events. It shows that both poorer and better-off households are exposed to potentially hazardous events. This is due to a significant inflow of households from the latter strata that are attracted by the favourable location at the foothills of the Andean mountains. The study concludes with a set of lessons to be learned from the findings for land use planning and zoning.